2023
DOI: 10.1002/ange.202316825
|View full text |Cite
|
Sign up to set email alerts
|

Markovnikov‐Selective Cobalt‐Catalyzed Wacker‐Type Oxidation of Styrenes into Ketones under Ambient Conditions Enabled by Hydrogen Bonding

Naba Abuhafez,
Andreas W. Ehlers,
Bas de Bruin
et al.

Abstract: The replacement of palladium catalysts for Wacker‐type oxidation of olefins into ketones by first‐row transition metals is a relevant approach for searching more sustainable protocols. Besides highly sophisticated iron catalysts, all the other first‐row transition metal complexes have only led to poor activities and selectivities. Herein, we show that the cobalt‐tetraphenylporphyrin complex is a competent catalyst for the aerobic oxidation of styrenes into ketones with silanes as the hydrogen sources. Remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…While investigating the potential for the catalysis of cobalt­(III) complexes 2 and 3 , ,, we found that in the presence of PhSiH 3 and dioxygen, 2-vinylnaphthalene ( 9a ) could be oxidized to the corresponding ketone ( 10a ) in a Wacker oxidation-type fashion (cf. Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While investigating the potential for the catalysis of cobalt­(III) complexes 2 and 3 , ,, we found that in the presence of PhSiH 3 and dioxygen, 2-vinylnaphthalene ( 9a ) could be oxidized to the corresponding ketone ( 10a ) in a Wacker oxidation-type fashion (cf. Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Important contributions in this direction are nickel- and iron-based catalysts to promote the Wacker-type oxidation of olefins (Scheme b,c). A dual catalytic system involving a cobaloxime and an acridinium photocatalyst that yielded the anti-Markovnikov products under milder conditions was also recently reported (Scheme d) . With few exceptions (Scheme e), previous reports on Co-mediated oxidation of olefins to ketones, in a Markovnikov fashion, either suffer from limitations in scope, require harsh conditions, or lead to unspecific reactivity. , Some works also showed that, in the presence of Co and dioxygen, olefins can undergo oxidative cleavage, rather than oxidative hydration. , …”
Section: Introductionmentioning
confidence: 99%